2017
DOI: 10.1021/acsami.7b12128
|View full text |Cite
|
Sign up to set email alerts
|

Pushing the Limits of Piezoresistive Effect by Optomechanical Coupling in 3C-SiC/Si Heterostructure

Abstract: This letter reports a giant opto-piezoresistive effect in p-3C-SiC/p-Si heterostructure under visible-light illumination. The p-3C-SiC/p-Si heterostructure has been fabricated by growing a 390 nm p-type 3C-SiC on a p-type Si substrate using the low pressure chemical vapor deposition (LPCVD) technique. The gauge factor of the heterostructure was found to be 28 under a dark condition; however, it significantly increased to about -455 under illumination of 635 nm wavelength at 3.0 mW/cm. This gauge factor is over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Silicon carbide (SiC) is one of the most favorable wide bandgap semiconductor materials owing to its superior mechanical and electrical properties, as well as high resistance to thermal and chemical stress [5], [6]. Among 200 polytypes of SiC, only 3C polytype can be grown epitaxially on a large Si-substrate at around 1000 • C and hence the cost of the wafer reduces significantly [7], [8]. By taking the advantages of silicon-orientated mature MEMS processing technologies, 3C-SiC on the Si structure has opened a new platform to develop a wide range of better and low cost highly sensitive physical sensors for harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…Silicon carbide (SiC) is one of the most favorable wide bandgap semiconductor materials owing to its superior mechanical and electrical properties, as well as high resistance to thermal and chemical stress [5], [6]. Among 200 polytypes of SiC, only 3C polytype can be grown epitaxially on a large Si-substrate at around 1000 • C and hence the cost of the wafer reduces significantly [7], [8]. By taking the advantages of silicon-orientated mature MEMS processing technologies, 3C-SiC on the Si structure has opened a new platform to develop a wide range of better and low cost highly sensitive physical sensors for harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Among the more than 200 poly-types of SiC, 3C-SiC is the most preferable poly-type for MEMS devices as it can be readily grown on a large commercial Si-substrate. 4,5 Hence, the cost of a wafer is reduced signicantly and, most importantly, 3C-SiC is compatible with conventional N/MEMS technologies. 6,7 The proper metallization of any device is very important to obtain exact and accurate responses.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we have reported that the as-grown SiC film on a Si wafer is single crystalline 3C-SiC and its crystallographic orientation is (100) by selected area diffraction (SAD) and X-ray powder diffraction (XRD) measurements, respectively. [15] Due to the mismatch in lattice constant and thermal expansion of SiC and Si, we observed the stacking fault defects at the SiC/Si interface. However, the stacking faults are mainly distributed within 50 nm from the SiC/Si interface and the crystallinity significantly improved with increasing SiC film thickness.…”
Section: Introductionmentioning
confidence: 87%